PENGARUH INFORMASI LABA DAN KOMPONEN ARUS KAS TERHADAP HARGA SAHAM (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di BEI Periode Tahun 2009-2012) - Eva Janu Persiana, 11.05.52.0060; Aini, Nur (Students Journal of Accounting and Banking, 2015)
The purpose of this study was to examine and analyze the effect of earnings information and components of cash flow consisting of operating cash flow, cash flow investment, and financing cash flows to the stock price on manufacturing companies listed in Indonesia Stock Exchange 2009-2012 period. The samples in this study using purposive sampling technique, so it was chosen as many as 315 companies. The data in this study is secondary data obtained from the Indonesian Stock Exchange (IDX). Statistical methods used to analyze data using multiple regression analysis. The variables used were accounting profit, cash flow component that operating cash flows, investment cash flow, cash flow financing as the independent variable, while the share price as the dependent variable. Of testing hypotheses, this study resulted in the finding that the variable accounting profit, operating cash flow, cash flow and cash flow financing investments have a significant positive effect on stock prices.Keywords: Information Profit, Cash Flow Component, and Stock Prices